Posttraumatic Growth and Psychological Distress among Female Breast Cancer Survivors in India: A Cross-Sectional Study - Thakur, Monika; Sharma, Roopali; Mishra, Anand Kumar; Singh, Kulranjan (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Breast cancer survivors (BCS) may experience a cascade of negative reactions during the entire treatment process in the form of psychiatric morbidity. However, exposure to a traumatic event also has the fertile ground for the potential to catalyze a host of positive changes, including development in personal, interpersonal, and spiritual levels, commonly referred to as posttraumatic growth (PTG). PTG is defined as “positive psychological change experienced due to a struggle with highly challenging life circumstances.”Objective This study aims to measure the prevalence and correlates of PTG among BCS.Materials and Methods It was a cross-sectional study carried in a tertiary care center of North India from January 2021 to April 2021. Total 700 BCS were approached and screened using the purposive sampling technique. Data were analyzed using the Statistical Package for Social Sciences, version 20.Results The mean age (standard deviation [SD]) of the patients was 43.14 (8.53) years. The mean (SD) PTG score was 37 (13.66). Among the subdomain of PTG, most respondents showed growth in personal strength, relating to others, followed by an appreciation of life, spiritual change, and less growth in new possibilities. PTG was found to be significantly positively correlated with treatment completion time (r = 2.260, p = 0.02) and negatively correlated with depression, anxiety, and stress (r = –0.152, p = 0.04; r = –0.145, p = 0.05; r = –0.162, p = 0.02).Conclusion Psychological morbidities must be addressed along with medical treatment of breast cancer so that growth post trauma can be further facilitated.
Keywords: breast cancer survivors; posttraumatic growth; psychological distress; depression; anxiety; women; body image disturbances